Oxygen for Intrauterine Resuscitation of Unproved Benefit and Potentially Harmful. Issue 3 (September 2015) - Hamel, M.S.; Anderson, B.L.; Rouse, D.J.
Abstract : ( Am J Obstet Gynecol. 2014;211(2):124–127)